2018
DOI: 10.1021/acs.jpcc.8b03769
|View full text |Cite
|
Sign up to set email alerts
|

Polytriphenylamine Derivative and Carbon Nanotubes as Cathode Materials for High-Performance Polymer-Based Batteries

Abstract: Composites of polytriphenylamine (PTPA), its novel derivative poly­(4-carbamoyl-N,N-diphenylaniline-2,2,5,5-tetramethyl-pyrrolin-1-oxyl) (PTPA-PO), and multiwalled carbon nanotubes (CNTs) were synthesized by in situ polymerization. The characterization results showed that the CNTs were homogeneously distributed in the polymer matrix and formed a cross-linked conductive network. The electrical properties of PTPA/CNT composites were better than those of traditional acetylene black as conductive agents. Electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The overall capacity was 120 mAh g −1 , losing 10 % over 100 cycles. Subsequently, the same group attempted to enhance the electrochemical performance by the introduction of MWCNTs, but no significant improvement was achieved . A polymer of the 1,1,3,3‐tetramethylisoindolin‐2‐yloxyl radical showed a comparable performance in a lithium‐ion cell, whereas a polyphosphazene bearing an N‐tert ‐butyl‐ N ‐oxylamino phenyl radical unit resulted in a higher initial capacity of 145 mAh g −1 but a capacity drop of 35 % during the first 50 cycles .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall capacity was 120 mAh g −1 , losing 10 % over 100 cycles. Subsequently, the same group attempted to enhance the electrochemical performance by the introduction of MWCNTs, but no significant improvement was achieved . A polymer of the 1,1,3,3‐tetramethylisoindolin‐2‐yloxyl radical showed a comparable performance in a lithium‐ion cell, whereas a polyphosphazene bearing an N‐tert ‐butyl‐ N ‐oxylamino phenyl radical unit resulted in a higher initial capacity of 145 mAh g −1 but a capacity drop of 35 % during the first 50 cycles .…”
Section: Methodsmentioning
confidence: 99%
“…A cell based on a polytriphenylamine and a graphite electrode and a potassium hexafluorophosphate‐based electrolyte was demonstrated, displaying a stable voltage but a low capacity of 60 mAh g −1 and a coulombic efficiency of only 80 % . Dong and co‐workers prepared a polytriphenylamine on MWCNTs via in situ polymerization of triphenylamine in a dispersion of MWCNTs . Subsequently, the authors built a hybrid lithium‐ion cell without additional conductive additives, which revealed a stable voltage of 3.7 V and a capacity of 100 mAh g −1 , retaining 85 % after 100 cycles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another solution is to attach radicals to a conductive skeleton, for example, polytriphenylamine (PTPA) [26]. Dong's and Zhang's groups attached 2,2,5,5-tetramethyl-3-pyrrolin-1-oxyl (PO) and 2,2,6,6-tetramethylpiperidiny-N-oxyl (TEMPO) to PTPA, respectively [27][28][29], which presented both p-type and n-type reactions in the favor of conductive PTPA. Unfortunately, the introduced PTPA skeleton decreased the theoretical capacity (~180 mAh g À1 ), which is much lower than poly (2,2,6,6-tetramethylpiperidinyloxy methacrylate (PTMA) (223 mAh g À1 ).…”
mentioning
confidence: 99%